Acrocallosal syndrome in a young hypertensive male. (3rd May 2011) - Ramteke, Vishal V; Darole, Pramod A; Shaikh, Zohaib Farooqui; Padwal, Namita J; Agrawal, Brijesh; Shrivastava, Makardhwaj S; Kamath, Sandhya
Abstract : Acrocallosal syndrome is an extremely rare genetic disorder with autosomal recessive inheritance. It is characterised by moderate to severe mental retardation, hypotonia, agenesis of the corpus callosum and preaxial polydactyly involving both feet and the facial features like broad forehead and hypertelorism. The authors report a case of a young hypertensive male who presented with unprovoked seizures for the first time who had multiple craniofacial, digital dysmorphic features with moderate mental retardation. The diagnosis of acrocallosal syndrome was arrived at after neuroimaging showed agenesis of corpus callosum with interhemispheric cysts.